Gender Influences on Parent-Child Science Problem-Solving Behaviors. Issue 3 (2nd July 2016) - Short-Meyerson, Katherine; Sandrin, Susannah; Edwards, Chris
ABSTRACT: Gender is a critical social factor influencing how children view the world from very early childhood. Additionally, during the early elementary years, parents can have a significant influence on their child's behaviors and dispositions in fields such as science. This study examined the influence of parent gender and child gender on 2nd- and 4th-grade children's strategies for solving science problems with their parents, as well as their attitudes about science. The behaviors of 13 parent-child dyads as they solved hands-on science problems together in an informal setting were examined. A child interview and a parent questionnaire were used to elicit information about their attitudes toward life science compared to physical science. Quantitative and qualitative analyses of the parent-child interactions revealed differences in the amount of encouragement offered to boys versus girls. Additionally, there were differences in questioning behaviors by parents as a function of parent gender and child gender. Furthermore, parental interest in various science topics differed along traditional gender roles, whereas boys and girls were interested in topics from both disciplines.